Using Contextual Speller Techniques and Language Modeling for ESL Error Correction - Gamon, Michael; Gao, Jianfeng; Brockett, Chris; Klementiev, Alexander; Dolan, Bill; Belenko, Dmitriy; Vanderwende, Lucy (Proceedings of IJCNLP, Hyderabad, India, 2008)
We present a modular system for detection and correction of errors made by non-native (English as a Second Language = ESL) writers. We focus on two error types: the incorrect use of determiners and the choice of prepositions. We use a decision-tree approach inspired by contextual spelling systems for detection and correction suggestions, and a large language model trained on the Gigaword corpus to provide additional information to filter out spurious suggestions. We show how this system performs on a corpus of non-native English text and discuss strategies for future enhancements.